Interpréter dans la grosseur du trait - François-Joseph Daniel (Revue d'anthropologie des connaissances)
Dispersion models are currently one of the major implementation tools of odorous nuisance regulation. Their recurrent mobilisation in newly established industrial facilities brings to the fore issues regarding their use in specific scientific, economic and institutional contexts. More particularly, these issues raise the following questions: how is trust developed in these models? How do users cope with the models’ inherent uncertainties? And how do the simulation results capture and impact reality. This article shows that odour dispersion models are used as black boxes to generate visual cartographical representations whose purpose is to foresee and evaluate odour nuisance. These cartographies are born of –and driven by– a “culture of simulation” (Sundberg, 2010) in which they are used only for their results. Practices differ, however, depending on the context in which the devices are used. On the one hand, when models serve to predict odour nuisance (before the facilities are set up), they operate as uncontested and performative instruments that equip impact assessments. They give life to the nuisance, make it real, from an institutional viewpoint. On the other hand, when the models are used to evaluate the nuisance, in the context of an already established and functioning facility, the discrepancies between the model results and the local residents’ experiential perceptions create a need for model validation in context. Furthermore, these discrepancies result in a more prudent use of simulations as an indication rather than a strict representation of reality, and necessitate the mobilisation of other complementary methods to qualify the odorous pollution.